Recovering metallic Pb directly from lead smelting dust by NaOH-carbon roasting process - Jingxin Liu (Journal of Materials Research and Technology, 2020)
Systematic chemical and mineralogical analyses were conducted for the dust generated in the Shuikoushan (SKS) lead smelting process, based on the results, an alternative strategy of direct metallic Pb recovery was proposed using NaOH–carbon roasting process. The reduction thermodynamics of PbSO4 was discussed, and the influencing parameters, including NaOH/dust mass ratio, carbon/dust mass ratio, roasting temperature and roasting time, were investigated systematically by experiments. The results indicated that increasing in the operation conditions was beneficial for the improved Pb recovery rate, and the reaction mechanism in this study was presumed as PbSO4→ C PbS→ NaOH Pb. The optimal conditions were determined as NaOH/dust mass ratio of 1.0, carbon/dust mass ratio of 0.2, roasting temperature of 650 °C and roasting time of 180 min. Under these conditions, 87.33% of Pb in the dust was directly recovered as metal pellets, gathering 96.48% of Bi, and 97.06% of As was converted into the alkali solution, while Zn and Cd were retained in the leaching residue. This process is clean and environmentally friendly for recovery of secondary resources bearing high content of PbSO4.